Collaborations and Design Development of Local Craft Products: Service Design for Creative Craft Community - Rasa Suntrayuth (Graduate School of Institut Seni Indonesia Yogyakarta, 2016)
Local craft product is one of the key elements in expressing different identities of local culture in different countries. Local craft communities in Thailand have quite unique skills in producing different craft using local materials and techniques. However, the craft production is later facing the problem of missing their own identity. The products are also unable fit to the demand of international market. This research is a result of the co-creation project on developing local craft products which is a part of the research on a service design for creative craft community: A case study of Phanusnikom district, Chonburi province, Thailand. The benefits of this study will stimulate the development and preservation of local craft products and communities in a more sustainable way. This study aims to explore the possible methods of how designers, local craftsmen, academic institutions and local business clusters can collaborate and raise new opportunities for the communities to become a creative craft space. The study has concentrated on a case study of Phanusnikom District, Chonburi Province, Thailand where most of the people are creating wickerwork from bamboo. The data collected within the research come from ethnographic fieldwork, which consists of basic methods such as site visits and interviews. The research also includes the concept of Service design thinking and tools, which can help to analyze the data into different sets of relationship between service users, service providers, and environment. Groups of product design students, local craftsmen, local business clusters, professional designers, and artists are co – creating new craft products. The results express throughout the process which emphasize on presenting the ability of local craftsmen beyond what they are expected; exchanging knowledge; creating a more comfortable collaboration between the stakeholders; and strengthen the local craft community for more future sustainable developments.